2017
DOI: 10.1111/tops.12279
|View full text |Cite
|
Sign up to set email alerts
|

New Space–Time Metaphors Foster New Nonlinguistic Representations

Abstract: What is the role of language in constructing knowledge? In this article, we ask whether learning new relational language can create new ways of thinking. In Experiment 1, we taught English speakers to talk about time using new vertical linguistic metaphors, saying things like "breakfast is above dinner" or "breakfast is below dinner" (depending on condition). In Experiment 2, rather than teaching people new metaphors, we relied on the left-right representations of time that our American college student partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Given that in Mandarin most words expressing temporal past and future consist of past‐in‐front/future‐at‐back metaphors (Chen, ; Peng, ; Experiment 1), if habitual use of certain space–time metaphors can indeed influence one's time conceptions (Boroditsky, ; Hendricks, Bergen, & Marghetis, ; Hendricks & Boroditsky, ; Li, Casaponsa, Wu, & Thierry, ), one possibility is that, under the influence of past‐in‐front/future‐at‐back metaphors, some Mandarin speakers may form past‐in‐front/future‐at‐back space–time mappings in the long run. Especially, we did not find evidence for the effect of individual TFI (temporal focus index) on the temporal diagram placements within the Chinese participants in the neutral‐wording condition.…”
Section: Discussionmentioning
confidence: 99%
“…Given that in Mandarin most words expressing temporal past and future consist of past‐in‐front/future‐at‐back metaphors (Chen, ; Peng, ; Experiment 1), if habitual use of certain space–time metaphors can indeed influence one's time conceptions (Boroditsky, ; Hendricks, Bergen, & Marghetis, ; Hendricks & Boroditsky, ; Li, Casaponsa, Wu, & Thierry, ), one possibility is that, under the influence of past‐in‐front/future‐at‐back metaphors, some Mandarin speakers may form past‐in‐front/future‐at‐back space–time mappings in the long run. Especially, we did not find evidence for the effect of individual TFI (temporal focus index) on the temporal diagram placements within the Chinese participants in the neutral‐wording condition.…”
Section: Discussionmentioning
confidence: 99%
“…2 Interestingly, after learning Chinese vertical spatial metaphors, English speakers are also more inclined to think of time vertically (Boroditsky, 2001;Hendricks & Boroditsky, 2015). Additionally, Boroditsky found that Chinese speakers can conceptualise time vertically, even when they think in English.…”
Section: Theories Accounting For Chinese Vertical Gesturing About Timementioning
confidence: 99%
“…Answering “Friday” implies choosing the ego-moving perspective, because people would imagine themselves moving toward the future, hence “forward” is interpreted as moving in the direction from Wednesday to Friday. In contrast, answering “Monday” means choosing the time-moving perspective, because people would imagine the future moving toward them, hence “forward” is interpreted as moving in the direction that time is moving from Wednesday to Monday (Hendricks and Boroditsky, 2017). In recent studies, this method has been used extensively to investigate how people choose different time movement perspectives (Boroditsky and Ramscar, 2002; Margolies and Crawford, 2008; Hauser et al, 2009).…”
Section: Introductionmentioning
confidence: 99%